Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00705-012-1223-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection of honey bees with acute bee paralysis virus does not trigger humoral or cellular immune responses

Abstract: We have studied the responses of honey bees at different life stages (Apis mellifera) to controlled infection with acute bee paralysis virus and have identified the haemolymph of infected larvae and adult worker bees as the compartment where massive propagation of ABPV occurs. Insects respond with a broad spectrum of induced innate immune reactions to bacterial infections, whereas defence mechanisms based on RNA interference play a major role in antiviral immunity. In this study, we have determined that honey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 55 publications
(95 reference statements)
1
56
0
1
Order By: Relevance
“…However, there is contradictory evidence concerning the role of humoral immunity in combating viral infection. Azzami et al (2012) reported that antimicrobial peptide (e.g. hymenoptaecin and abaecin) expression is not altered upon viral challenge, while a more recent study showed that IAPV infection up-regulates multiple immune signaling pathways in adult bees (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is contradictory evidence concerning the role of humoral immunity in combating viral infection. Azzami et al (2012) reported that antimicrobial peptide (e.g. hymenoptaecin and abaecin) expression is not altered upon viral challenge, while a more recent study showed that IAPV infection up-regulates multiple immune signaling pathways in adult bees (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…No evidence for a negative association between immune gene expression and DWV titers was found, in contrast to an earlier study of adult honey bee workers (Yang and Cox-Foster, 2005), suggesting that an active suppression of DWV by the honey bee immune system is unlikely in this case. Instead, a few immune genes were positively associated with the virus titers (Boncristiani et al, 2013) and most did not show a significant association (Azzami et al, 2012). More research is needed to understand virus interactions with insect immunity (Costa et al, 2009;Flenniken and Andino, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Immunogene and viral transcript dynamics during parasitic Varroa destructor mite infection of developing honey bee (Apis mellifera) pupae Ryan D. Kuster, Humberto F. Boncristiani and Olav Rueppell* functioning of the honey bee immune system in response to viral infection is particularly understudied and no response (Azzami et al, 2012), immunosuppression (Nazzi et al, 2012) or upregulation of immunogenes (Boncristiani et al, 2013) has been reported. Honey bees respond to pattern recognition of bacterial and fungal molecules through the rapid expression of antimicrobial peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the mean abundance of mites, and thus, mite feeding pressure, was similar in GDCs and GSCs suggests differences in the immune responses of individual bees within GDCs and GSCs could also contribute to the observed differences in virus prevalence and concentration. Very little is known about the immune response of honey bees to viruses (Azzami et al 2012). However, bees can maintain viral infections without showing obvious disease symptoms (Bailey et al 1963), suggesting some kind of antiviral mechanisms prevent virus replication.…”
Section: Discussionmentioning
confidence: 99%